Entrepreneurial Management in Government and Business as a Path toward Innovation and Democracy - Sapparojpattana, Winaicharn (วารสารปัญญาภิวัฒน์, 2013)
Abstract Public and private organizations alike are social institutions under the same economic dynamism and the current of globalization. Public sector has learned how to do things right from private counterpart while business administration is learning how to do right things from public administration. From historical, economic and behavioral perspectives, this paper explores entrepreneurial management enacted in large corporations and in governments worldwide in the context of process, structure, culture and leadership. Its distinctive limitations and possible improvements within both sectors are then examined. The key sustainable success factors found from several theoretical frameworks to this managerial and structural convergence of entrepreneurship in public and private organizations include the similar path of accountability and transparency in their new social architectures. Keywords: Entrepreneurial Spirit, Economic Value, Public Value, Accountability, Transparency, Sustainability, Leadership. บทคัดย่อ องค์การของรัฐและของเอกชนต่างก็เป็นสถาบันทางสังคมภายใต้พลวัตทางเศรษฐกิจและกระแส โลกาภิวัตน์ องค์การในภาครัฐได้เรียนรู้แนวการเพิ่มประสิทธิภาพในการบริหารงานจากองค์การ ในภาคเอกชน ซึ่งก็กำลังศึกษาการสร้างประโยชน์เพื่อส่วนรวมจากการบริหารรัฐกิจเช่นเดียวกัน บทความนี้อาศัยการวิเคราะห์เชิงประวัติศาสตร์ เศรษฐศาสตร์ และพฤติกรรมศาสตร์ ทำความเข้าใจ กระบวนการ โครงสร้างองค์กร วัฒนธรรม และภาวะผู้นำในการบริหารอย่างเป็นผู้ประกอบการ ที่ดำรงคงอยู่ในบริษัทขนาดใหญ่และในหน่วยงานต่างๆ ของรัฐบาลทั่วโลก โดยมุ่งตรวจสอบถึง ข้อจำกัดของแนวคิดทางทฤษฎีและความเป็นไปได้ที่จะปรับปรุงการปฏิบัติตามรูปแบบของการจัดการอย่างเป็นผู้ประกอบการในภาครัฐและภาคเอกชนจากการทบทวนวรรณกรรมที่หลากหลายได้ค้นพบว่า แนวทางร่วมกันในการบริหารงานและการจัดองค์การตามอย่างการเป็นผู้ประกอบการ ในองค์การของรัฐและของเอกชนนั้นสามารถมุ่งไปสู่เป้าหมายเดียวกันได้ ทั้งนี้ด้วยการวางรูปแบบความสัมพันธ์ทางสังคมใหม่ภายในองค์กรที่มีความพร้อมรับผิดชอบและมีความโปร่งใสอยู่เสมอ คำสำคัญ: จิตวิญญาณของผู้ประกอบการ มูลค่าทางเศรษฐกิจ คุณค่าเพื่อส่วนรวม ความพร้อมรับผิดชอบ ความโปร่งใส ความยั่งยืน ภาวะผู้นำ